Os desafios para a concepção da política de gestão de pessoas humanizada: o caso da administração pública de Passo Fundo RS - Camargo, Evandro José Bilyez de (2017)
The constant search for contemporary processes, tools, policies and practices that allow a universe of greater interactivity, respect and responsibility with the management of people and that lead to humanization in the public sector seem to be increasingly relevant. The perception of managers, although considering the constitutional, economic-financial and fiscal precepts, tends to find in the social circles the reasons for achieving oriented by the efficiency, effectiveness and effectiveness of the employees. In relation to this, when it is determined the awareness of an excellent service delivery to society, it seems essential that the management will provide policies and practices that consider people as main actors, enabling, training, motivating, professionalizing and providing quality of Life to all. Based on this, this study proposed, through a case study research and content analysis, with a bibliographical, descriptive, documentary and qualitative character, to present the reality perceived in the city of Passo Fundo RS, with regard to the Universe of feelings and feelings of managers and servers in general in their daily activity. This was done in the period between August 1, 2016 and November 1, 2016, through interviews with eight secretaries and the mayor and a questionnaire applied in the universe of eighty servers. These observations sought to understand how people are and how they perceive what is happening in terms of work and recognition. With this, it can conclude that the municipal administration, although it has tried to meet some demands, regarding the requirements of attendance to its servants, does not seem to meet the great part of its anxieties in administrative terms. And this is due to the absence of policies and practices of people management, in addition to being identified almost nothing with regard to the ideals of humanization, as well as, a total absence of any structure or process that allows identifying strategic management. What tends to determine through the research, that few actions or projects, oriented to the attendance of the needs of the servers, can be identified. Therefore, with the course of this study and supported by the various relevant literature, at the end, it is presented as a suggestion, an organizational climate model. And this is intended to help municipal management, so that it can try to reproduce, which seems to be a fundamental premise when a modernized organization is determined and which advocates meeting the aspirations of society as a whole.